Understanding Black-African International Students’ Experiences in United States Colleges and Universities Through Social Identity Theory - Awuor, Diana Carole (Journal of International Students, 2020)
In this Research in Brief, Tajfel’s (1970) social identity theory is explained and examined as potentially useful for analyzing the experiences of Black-African international students in U. S. colleges and universities. Race has been and still is a major issue in the United States. Through a review of literature, I sought to find out how Black-African international students’ race affected their experiences in the United States.